Sviluppi attuali nella psicoterapia delle psicosi - Cantini, Andrea (Il sogno della farfalla, 2018)
The article describes the history of a Mental Health Department of ASL (Local Health Board) Roma D starting from the mid 1990s. After defining the meaning of the term “psychotherapy” and outlining what the term “psychosis” defines, the author tells about the challenge of facing severe mental illnesses with psychotherapy. After shortly describing the history of the psychotherapeutic management of psychosis in Europe and the US, the author puts forth a few theoretical and methodological considerations about the treatment approaches being carried out within Italian public health infrastructures. The fundaments of the psychotherapeutic practice, i.e. setting, transference and interpretation, are deeply expounded taking into account the relevant differences between private practices and the NHS infrastructures.